The contribution of crime to the longitudinal relationship between neighbourhood disadvantage and mental well-being, 2009 to 2016 - Davis, Emily M.; Heesch, Kristiann C.; Rachele, Jerome N.; Burton, Nicola W.; Turrell, Gavin (Social science & medicine (1982), 2025)
Actions to reduce neighbourhood-level socioeconomic inequities in mental well-being hinge on contemporary research exploring neighbourhood-level mechanisms, such as crime—a social factor widely known to be disproportionately distributed in disadvantaged neighbourhoods. We used longitudinal data from the HABITAT study (2009–2016) and random effects linear regression models to explore the contribution of objectively measured crime (crime against the person, social incivilities, unlawful entry) and a self-report indicator (perceptions of crime and safety) to the relationship between neighbourhood disadvantage and mental well-being, adjusting for neighbourhood self-selection and other time-varying (age, occupation, household income) and time-invariant (gender, education) covariates. People with greater concerns about crime and safety in their neighbourhood had poorer mental well-being. This partly explained the relationship between neighbourhood disadvantage and mental well-being. However, objectively measured crime did not contribute to this relationship. Adjustment for neighbourhood self-selection made little to no contribution to the neighbourhood disadvantage—mental well-being relationship. This study's findings suggest that policies and programs aimed at reducing concerns about crime and safety in disadvantaged neighbourhoods may provide an opportunity to reduce socioeconomic inequities in population mental well-being. •Perceptions of neighbourhood crime and safety matter for mental health.•Perceptions of crime partly explain socioeconomic inequities in mental well-being.•Police reported crime didn't explain socioeconomic inequities in mental well-being.•People more concerned about crime have poorer mental well-being.•Choice to live in a low crime area didn't change social inequities in mental health.